Challenges Facing Independent Cultural Actors: The Case of Egypt - Khedr, Reem (AUC Knowledge Fountain, 2021)
The independent art scene in Egypt flourished following the January 25 revolution in 2011. This study examines the experiences of Egyptian artists and cultural operators through a looking glass into the evolving democratization of arts towards cultural democracy from a global perspective and using the intrinsic and instrumentalist arguments regarding the value of arts. Furthermore, it employs a qualitative analysis of case studies of 18 cultural operators in Cairo and Alexandria, who work in different artistic fields ranging from visual arts to performing arts and academia. The results demonstrate that the cultural policy framework guiding the arts sector in Egypt has restricted the independent scene financially and legally by making survival of the artistic entities difficult and sustainability unrealistic. Interviews with different artists and cultural operators reveal that there is a lack of capacity building to prepare a qualified cadre of cultural leaders and managers. They also show pitfalls in arts education and a lack of artistic excellence. These pitfalls have affected accessibility of audience to arts and accessibility of emerging artists to audience and to venues. Moreover, the interviews highlight the struggle cultural operators face in maintaining a decent standard of living while working in a volatile field. Considering the aforementioned, this study indicates the negative consequences of vague cultural policies on the Egyptian independent art scene and goes further to make recommendations.